1998
DOI: 10.1074/jbc.273.2.842
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Domains of the p70 Ku Protein Mediating Dimerization with p80 and DNA Binding

Abstract: The Ku autoantigen is a heterodimer of 70 (p70) and ϳ80 kDa (p80) subunits that is the DNA-binding component of the DNA-dependent protein kinase (DNA-PK) complex involved in DNA repair and V(D)J recombination. Binding to DNA ends is critical to the function of DNA-PK, but how Ku interacts with DNA is not completely understood. To define the role of p70 and p80 and their dimerization in DNA binding, heterodimers were assembled by co-expressing the subunits using recombinant baculoviruses. Two p70 dimerization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 27 publications
8
76
0
Order By: Relevance
“…2B) and results in a frameshift and a premature termination codon. The 30 amino acid truncated product is predicted to lack regions of Ku70 that are essential for DNA binding and repair activity [27][28][29].Similar to the Ku70 atg MO, an increase in TUNEL-positive cells was seen in irradiated embryos injected with the Ku70 splice MO, but not the corresponding mismatched MO (Fig. 3I, J).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…2B) and results in a frameshift and a premature termination codon. The 30 amino acid truncated product is predicted to lack regions of Ku70 that are essential for DNA binding and repair activity [27][28][29].Similar to the Ku70 atg MO, an increase in TUNEL-positive cells was seen in irradiated embryos injected with the Ku70 splice MO, but not the corresponding mismatched MO (Fig. 3I, J).…”
mentioning
confidence: 70%
“…2B) and results in a frameshift and a premature termination codon. The 30 amino acid truncated product is predicted to lack regions of Ku70 that are essential for DNA binding and repair activity [27][28][29].…”
Section: Nih Public Accessmentioning
confidence: 99%
“…The Ku70 protein contains several functional domains, including the Ku86-binding sites (aa 1-115 and aa 378-482), DNA-binding domain (aa 277-341) and the C-terminal portion (aa 536-609). 16,17 The N-terminal portion (aa 1-535) is important for Ku70 to heterodimerize with Ku86 and bind to DNA to mediate its DSB repair capacity. The C terminus of Ku70 is mainly responsible for its antiapoptotic function, 20 through mechanism(s) that were not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The Ku70 protein consists of three structural domains, including the N-terminal, central (that is, DNA binding) and C-terminal domains. 16,17 Ku70 usually heterodimerizes with Ku86, which forms a functional complex for DSB repair. By forming a bridge between the broken DNA ends, the Ku70/Ku86 heterodimer acts to structurally support and align the DNA ends, to protect them from degradation and to prevent promiscuous binding to unbroken DNA.…”
mentioning
confidence: 99%
“…In addition, the interacting regions of Ku70 and Ku80 have not been shown to contain any motif previously reported to be necessary for protein-protein interactions (Koike et al, 1998). Recently, it has also been shown that the two putative leucine zipper motifs identi®ed in Ku70 were not required for its heterodimerization with Ku80, using recombinant baculovirus-expressed proteins (Wang et al, 1998).…”
Section: Introductionmentioning
confidence: 95%